Integrating Digitalization, Corporate Social Responsibility, and Human Capital for Environmental Sustainability: The Strategic Role of Green Finance in Commercial Banks - Ashfaq, Muhammad; Akhtar, Shamim; Akhlaq, Muhammad; Yousaf, Azeem; Ullah, Kafait (International Journal of Energy Economics and Policy, 2025)
This study investigates the determinants of environmental sustainability (ES) within the banking sector of emerging economies, focusing on the roles of employee green behavior (EGB), corporate social responsibility (CSR) initiatives, and green innovation (GI). It further examines green finance (GF) as a mediating mechanism through which these factors influence environmental sustainability, while financial technology (FinTech) is explored as a moderating variable that may strengthen or weaken these relationships. Empirical data were collected from 385 branch managers in the banking industry through a combination of self-administered and online survey questionnaires. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the direct and indirect correlations between the variables. The findings indicated that banks’ environmental sustainability was positively and significantly impacted by their sponsorship of green projects. Furthermore, it was found that banks’ sustainable performance is improved by CSR initiatives and green employee behavior, and that FinTech does not moderate the relationship between environmental sustainability and green innovations through the mediation of green finance. This study is unusual because it examines the combined effects of employee green behavior, green innovations, CSR initiatives, green financing, and Fintech adoption on sustainability—an area that hasn’t gotten much attention in previous research. In particular, this study supports the 2030 Agenda for Sustainable Development by showing how financial technologies and sustainable banking practices help achieve SDG 9 (Industry, Innovation, and Infrastructure) and SDG 13 (Climate Action), two UN Sustainable Development Goals.